Categorical perception of familiarity: Evidence for a hyper-familiarity in schizophrenia. (December 2015) - Horn, Mathilde; D'Hondt, Fabien; Vaiva, Guillaume; Thomas, Pierre; Pins, Delphine
Abstract: Familiarity is a crucial aspect of recognition that may be perturbed in schizophrenia patients (SZP) and may lead to delusional disorders. However, there are no existing guidelines on how to assess and treat familiarity disorders in schizophrenia. Some experimental studies have investigated familiarity processing in SZP but have produced inconsistent results, which are likely a result of methodological issues. Moreover, these studies only assessed whether familiarity processing is preserved or impaired in SZP, but not the tendency of SZP to consider unfamiliar stimuli to be familiar. By using a familiarity continuum task based on the existence of the categorical perception effect, the objective of this study was to determine whether SZP present hyper- or hypo-familiarity. To this purpose, 15 SZP and 15 healthy subjects (HS) were presented with facial stimuli, which consisted of picture morphs of unfamiliar faces and faces that were personally familiar to the participants. The percentage of the familiar face contained in the morph ranged from 5 to 95%. The participants were asked to press a button when they felt familiar with the face that was presented. The main results revealed a higher percentage of familiarity responses for SZP compared with HS from the stimuli with low levels of familiarity in the morph and a lower familiarity threshold, suggesting a hyper-familiarity disorder in SZP. Moreover, the intensity of this "hyper-familiarity" was correlated with positive symptoms. This finding clearly suggests the need for a more systematic integration of an assessment of familiarity processing in schizophrenia symptoms assessments. Graphical abstract: Highlights: Familiarity processing was assessed in schizophrenia patients. A familiarity continuum task was conducted using an imaging-morphing procedure. A hyper-familiarity disorder was observed in schizophrenia patients. This hyper-familiarity was correlated with positive symptoms. A more systematic assessment of familiarity in schizophrenia is necessary.